Description of a New Species of the Genus Psectrosciara and a New Record of Parascatopse sonorensis (Diptera: Scatopsidae) From Florida. Issue 1 (29th July 2015) - Huerta, Heron; Hribar, Lawrence J.
Abstract : Psectrosciara floridensis sp. nov. belonging to the scatopsiformis group is described and illustrated. This species is closely related to Psectrosciara scatopsiformis Enderlein, 1912, Psectrosciara californica (Cole, 1912), Psectrosciara brevipennis Cook, 1958, and Psectrosciara serrata Cook, 1958. A new record of Parascatopse sonorensis Cook is reported from the state of Florida.